The cardiovascular response to exercise in athletes recovering from SARS-CoV-2 infection: A prospective cohort study with repeated measures over 16 weeks - AWARE IX - Kaulback, K.; Schwellnus, M.; Sewry, N.; Lombard, C.; Jordaan, E.; Wood, P. (Journal of Sports Sciences, 2023)
Higher exercise heart rate (HR) and prolonged return-to-sport in athletes with SARS-CoV-2 infection are described, but the cardiovascular response to exercise during recovery is not understood. This prospective, cohort, experimental study with repeated measures evaluated the cardiovascular response to exercise over 16 weeks in athletes recovering from SARS-CoV-2 infection. Athletes (n = 82) completed 2-5 repeat assessments at regulated intervals over 16 weeks post-SARS-CoV-2 infection. Data from 287 assessments (submaximal exercise tests; Modified Bruce protocol) are included. HR (bpm), systolic blood pressure (SBP) (mmHg) and rating of perceived exertion (RPE) (Borg scale 6-20) were measured. Rates of change in HR, SBP and RPE over time are reported. Submaximal exercise HR, SBP and RPE decreased significantly over 16 weeks (p < 0.01). There was a steeper rate of decline for HR and RPE =30 days compared to >30 days after SARS-CoV-2 infection: HR at Stage 3: =30 days -0.53 (0.01); >30 days -0.06 (0.02) and Stage 5: =30 days -0.77 (0.12); >30 days -0.12 (0.02); RPE at Stage 3: =30 days -0.09 (0.02); >30 days -0.01 (0.0002) and Stage 5: =30 days -0.13 (0.02); >30 days -0.02 (0.004). The findings provide clinical recommendation for exercise prescription and monitoring RPE in response to exercise post-SARS-CoV-2 infection and contribute to the clinical understanding of recovery which can help manage athlete expectations.